Teaming up in primary care: Membership boundaries, interdependence, and coordination. Issue 2 (February 2022) - Everett, Christine M.; Docherty, Sharron L.; Matheson, Elaine; Morgan, Perri A.; Price, Ashley; Christy, Jacob; Michener, Lloyd; Smith, Valerie A.; Anderson, John B.; Viera, Anthony; Jackson, George L.
ABSTRACT: Objective: Increased demand for quality primary care and value-based payment has prompted interest in implementing primary care teams. Evidence-based recommendations for implementing teams will be critical to successful PA participation. This study sought to describe how primary care providers (PCPs) define team membership boundaries and coordinate tasks. Methods: This mixed-methods study included 28 PCPs from a primary care network. We analyzed survey data using descriptive statistics and interview data using content analysis. Results: Ninety-six percent of PCPs reported team membership. Team models fell into one of five categories. The predominant coordination mechanism differed by whether coordination was required in a visit or between visits. Conclusions: Team-based primary care is a strategy for improving access to quality primary care. Most PCPs define team membership based on within-visit task interdependencies. Our findings suggest that team-based interventions can focus on clarifying team membership, increasing interaction between clinicians, and enhancing the electronic health record to facilitate between-visit coordination.